Regulation of uncovered sovereign credit default swaps – evidence from the European Union. Issue 4 (17th August 2015) - Kiesel, Florian; Lücke, Felix; Schiereck, Dirk
Abstract : Purpose: – This study aims to analyze the impact and effectiveness of the regulation on the European sovereign Credit Default Swap (CDS) market. The European sovereign debt crisis has drawn considerable attention to the CDS market. CDS have the ability of a speculative instrument to bet against a sovereign default. Therefore, the Regulation (EU) No. 236/2012 was introduced as the worldwide first uncovered CDS regulation. It prohibits buying uncovered sovereign CDS contracts in the European Union (EU). Design/methodology/approach: – First, this paper measures spread changes of sovereign CDS of the EU member states around regulation specific event dates to detect whether and when European sovereign CDS reacts to regulation announcements and the enforcement of regulation. Second, it compares the CDS long-term stability of the EU sample with a non-EU sample based on 44 non-EU sovereign CDS entities. Findings: – The results indicate widening CDS spreads prior to the regulation, and stable CDS spreads following the introduction of the regulation. In particular, sovereign CDS of European crisis-hit entities are stable since the regulation was introduced. Originality/value: – The results show that since the regulation of uncovered CDS in the EU has been enacted, the sovereign CDS market is stable and less volatile. Based on the theory about speculation on uncovered sovereign CDS by betting on the reference entity's default, the introduction of Regulation (EU) No. 236/2012 appears to be an appropriate measure to stabilize markets and reduce speculation on sovereign defaults.